Chronic cough and weight loss in an adolescent marijuana smoker. (March 2022) - Onorato, Angela; Shapiro, Jana; Griffin, Lindsay; Aldulescu, Monica; Arva, Nicoleta C; Shah, Avani
Marijuana is the most widely used illicit drug in the United States. As marijuana becomes legalized in more states and its use increases among adolescents, pediatricians must be aware of the impact of marijuana on pediatric health. Marijuana smoking as well as cigarette smoking has been associated with numerous lung diseases, including chronic bronchitis and bullous lung diseases. This case report postulates that regular marijuana smoking may be associated with pulmonary Langerhans cell histiocytosis, a severe lung disease that lacks definitive treatment and can cause respiratory failure. Given the potential risk of life-threatening lung diseases, pediatricians must screen adolescents with respiratory symptoms for marijuana use. In addition, this case underscores the need for further research and improved understanding of the relationship between marijuana smoking and lung disease.